Forty‐five years on home hemodialysis, a case of exceptional longevity. Issue 4 (5th September 2019) - Abdul Salim, Sohail; Cheungpasitporn, Wisit; Echols, Vonda; Monga, Divya; Davidson, Jamie; Juncos, Luis A.; Fülöp, Tibor
Abstract: End‐stage renal disease is associated with dismal long‐term survival in general. Home hemodialysis (HHD) has been advocated as a modality affirming better quality of life and longer survival. We report a 62‐year‐old Caucasian female with end‐stage renal disease who has been exclusively on HHD for a total of 45 years, utilizing various platforms over the years. She has been one of the first home dialysis patients of the founding father of renal dialysis in the state of Mississippi, John D. Bower and cared by him throughout his career. Throughout this period, her life bore witness to the evolving technology of dialysis accesses, platforms, and evolution of HHD in its entirety. After review of the literature, we find that the longest vintage time on HHD documented to date was around 35 years. This extraordinary longevity bears testimony to the extraordinary self‐motivation of the patient, the dedication of her providers and the true potential of HHD in motivated subjects.